2022
DOI: 10.4314/ijbcs.v16i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation phytochimique et étude de l’activité antimicrobienne d’extraits de feuilles de trois plantes de la flore sénégalaise : Detarium senegalense, Detarium microcarpum et Piliostigma reticulatum

Abstract: Detarium senegalense, Detarium microcarpum et Piliostigma reticulatum sont trois plantes de la flore sénégalaise, utilisées en médecine traditionnelle pour la prise en charge de maladies infectieuses. Cette étude visait à déterminer in vitro l’activité antimicrobienne d’extraits et de fractions de feuilles de ces plantes sur différentes souches (Escherichia coli, Klebsiella oxytoca, Pseudomonas aeruginosa, Enterococus faecalis, Staphylococcus aureus et Candida albicans). Les méthodes de diffusion en milieu sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The results of Sanni et al [7] which show the presence of alkaloids, tannins and flavonoids, among others. The results of Elhadji et al [5] also reveal the presence of tannins, flavonoids, terpenes and steroids. These results are also similar to our own, despite some analyses that we did not carry out.…”
Section: Phytochemical Screeningmentioning
confidence: 88%
See 2 more Smart Citations
“…The results of Sanni et al [7] which show the presence of alkaloids, tannins and flavonoids, among others. The results of Elhadji et al [5] also reveal the presence of tannins, flavonoids, terpenes and steroids. These results are also similar to our own, despite some analyses that we did not carry out.…”
Section: Phytochemical Screeningmentioning
confidence: 88%
“…With this in mind, we focused our study on Detarium senegalense, a plant easily found in southern Chad. In pharmacology, the seed coats of Detarium senegalense are used in Nigeria to treat arrow poisoning, while in Senegal, the burnt seeds are used as a mosquito repellent [4]. Fractions of the hydroethanol extract of Detarium senegalense bark have antibacterial activity against a wide range of pathogenic bacteria [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation